Uncivil mirth : ridicule in enlightenment Britain - Carroll, Ross, 1981- (Princeton University Press, 2021)
"Ridicule is a ubiquitous feature of modern politics. Few participants in a political contest can resist the temptation to ridicule their opponents in order to demean them, persuade others to regard them with scorn, or expose their hypocrisy. Yet ridicule also has the potential to undermine the conditions necessary for politics itself, converting disputants into belligerents and debate into the silence of mutual disdain. Unsurprisingly, then, ridicule has not only been common in political debate but has often been at the centre of such debate as well. In contemporary debate, some commentators worry that citizens are reaching for ridicule and contemptuous dismissal at the expense of more earnest forms of political engagement. Theorists of deliberative democracy have warned that there might be something inherently uncivil, trivializing, or morally objectionable about the use of ridicule in political debate. Others are more inclined to accept that a society characterized by vibrant political contestation will not lack for ridiculers deriding, shaming, and insulting each other. They counsel that ridicule is more urgent, and necessary, now than ever, particularly as a weapon against authoritarian personalities who are least able to tolerate it. This book brings some much-needed historical contextualization to this debate by revisiting a moment in which the place of ridicule in politics was subjected to more intense theoretical scrutiny than any other: eighteenth-century Britain. The relaxing of censorship and deregulation of the printing trade in the 1690s led to an explosion of political and religious satires, many of which were mobilized in the political contest over the recently passed Toleration Act. This new vogue for ridicule led numerous critics to warn that indulging in it excessively could disfigure one's character, undermine religion, and sow civil discord. But ridicule also had vocal defenders, none more influential than the Third Earl of Shaftesbury. Far from merely accepting ridicule as the unfortunate by-product of free public debate, Shaftesbury defended the "trial of ridicule" as a useful method for exposing the conceitedness of fanatics and overly zealous clerics, the two groups most threatening to toleration. From David Hume to Mary Wollstonecraft, Carroll traces Shaftesbury's impact, examining how the Earl's many followers and critics throughout the eighteenth century responded to the challenge of using ridicule responsibly in political and religious controversy"--